2003
DOI: 10.1007/s10038-003-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 458 single nucleotide polymorphisms of disease candidate genes in the Korean population

Abstract: Single nucleotide polymorphisms (SNPs) are considered as very promising genetic markers for complex disease gene hunting. However, it has been demonstrated that there are significant ethnic differences in genetic variations. In order to investigate the genetic variations in the Korean population and their ethnic differences, a large number of SNPs of 161 disease candidate genes were collected from a publicly available SNP database and then tested for the distribution of allele frequency in the Korean populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The data suggest that the genetic origins of the Korean population are distinct from other ethnic populations, but very similar to the Japanese. The results reconfirm that extensive verification of public SNPs in a particular population is required prior to association studies, as reported previously [20]. …”
Section: Discussionsupporting
confidence: 68%
“…The data suggest that the genetic origins of the Korean population are distinct from other ethnic populations, but very similar to the Japanese. The results reconfirm that extensive verification of public SNPs in a particular population is required prior to association studies, as reported previously [20]. …”
Section: Discussionsupporting
confidence: 68%
“…Because previously reported restriction enzyme analyses of polymerase chain reaction (PCR) were not available, genotyping for A400V, V667M, R1036Q and A1525V polymorphisms was performed by SNP-IT™ assays using the SNP stream 25K™ System (Orchid Biosciences, New Jersey, U.S.A.) (22). Briefly, the genomic DNA region spanning the polymorphic site was PCR-amplified using one phosphothiolated primer and one regular PCR primer.…”
Section: Methodsmentioning
confidence: 99%
“…SNP Genotyping for Allele Frequency SNP genotyping was performed by SNP-IT assays with the SNPstream 25K System (Orchid Biosciences, Princeton, New Jersey) as previously described [10]. Briefly, the genomic DNA region spanning the polymorphic site was PCR-amplified with one phosphothiolated primer and one regular PCR primer.…”
Section: Materials and Methods Genomic Dna Isolation And Samplesmentioning
confidence: 99%